Evaluating the Implementation of Musyarakah Mutanaqisah in Enhancing Mortgage Financing Practices at Islamic Financial Institutions - Azizah, Fika Nurul; Subali, Subali (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study examines the evaluating effectiveness of musyarakah mutanaqishah financing at BPR Syariah Harta Insan Karimah, East Jakarta Branch, aimed at supporting asset ownership for community members in need. Despite its potential benefits, the process faces challenges due to payment delays from some customers. This research employs a participatory observation approach, utilizing qualitative descriptive methods with data collected through interviews and documentation. Findings indicate that BPR Syariah Harta Insan Karimah applies a profit-sharing scheme tailored for housing ownership, aligning with standard practices in Islamic banking. However, the bank enforces stringent credit evaluations, including a comprehensive review of customer credit history, to mitigate default risk. Customers with substantial arrears from other banks are ineligible for musyarakah mutanaqishah financing, reflecting the institution's commitment to prudent financing management. This study contributes to a better understanding of the operational standards and risk management strategies within sharia-based financial institutions.